Possibility for hedging from price increases in residential energy demand - Bente Halvorsen; Bodil M. Larsen (Statistics Norway, Research Department, 2003)
Liberalisation of the Norwegian electricity market has given more short-term variation in the electricity price. Since almost three quarters of Norwegian households have heating equipment using more than one energy carrier, we would expect them to be able to hedge from price increases and benefit from low prices by switching between energy carriers. In many studies estimates of the cross price derivatives in Norwegian residential energy consumption give a negative sign. The question is whether hedging is possible despite this negative sign, that is, if energy goods are alternatives and not separable in consumption. To answer this question, we estimate a conditional demand model on a sample of 2438 households to decompose the cross price derivatives. We find that the negative cross price derivatives are mainly due to budget effects. We also reject the hypothesis of weak separability, indicating that Norwegian households are able to hedge from energy price variations.
Keywords: D12; Q41; 330; Residential energy demand; empirical microanalysis; separability test